Pharmaceutical microscopy - Carlton, Robert Allen (Springer, 2011)
Microscopy plays an integral role in the research and development of new medicines. Pharmaceutical Microscopy describes a wide variety of  techniques together with numerous practical  applications of importance in drug development. The first section  presents general methods and applications with an emphasis on the physical science aspects. Techniques covered include optical crystallography, thermal microscopy, scanning electron microscopy, energy dispersive x-ray spectrometry, microspectroscopy (infrared and Raman), and particle size and shape by image analysis. The second section presents applications of these techniques to specific topics of pharmaceutical interest, including studies of polymorphism, particle size and shape analysis, and contaminant identification.  Pharmaceutical Microscopy is designed for those scientists who must use these techniques to solve pharmaceutical problems but do not need to become expert microscopists.  Consequently, each section has exercises designed to teach the reader how to use and apply the techniques in the book.  Although the focus is on pharmaceutical development, workers in other fields such as food science and organic chemistry will also benefit from the discussion of techniques and the exercises. Provides comprehensive coverage of key microscopy techniques used in pharmaceutical development Helps the reader to solve specific problems in pharmaceutical quality assurance Oriented and designed for pharmaceutical scientists who need to use microscopy but are not expert microscopists Includes a large number of practical exercises to give the reader hands-on experience with the techniques Written by an author with 21 years of experience in the pharmaceutical industry.